This action might not be possible to undo. Are you sure you want to continue?

Welcome to Scribd! Start your free trial and access books, documents and more.

Find out moreIn the ﬁrst line we introduced a convergence factor exp(λt

) with λ >0.

After the integration we will let λ →0. This procedure damps the rapid

oscillations of the integrand when the integration variable t

→−∞. Math-

ematicians might have something to say about exchanging integration and

taking the limit, but physicists plough ahead and see what happens. When

we let t

1

→−∞and λ →0, Equation (2.85) becomes

e

i(ω

+E

I

−E

A

)t

i(ω

+E

I

−E

A

)

(2.86)

Likewise we get for the integral over t

**in the second term of Equation (2.84)
**

_

t

t

1

dt

e

i(−ω+E

I

−E

A

)t

=

e

i(−ω+E

I

−E

A

)t

i(−ω +E

I

−E

A

)

(2.87)

Again, we note the structure of Equation (2.86) and Equation (2.87) when

comparing them.

We substitute Equation (2.86) and Equation (2.87) in Equation (2.84)

to get

λ

2

˙ c

(2)

f

(t) =

_

−

e

m

_

2

4π

2V

√

ωω

1

i

I

_

_

B

¸

¸

ε

λ

(k) · p

¸

¸

I

__

I

¸

¸

ε

∗

λ

(k

) · p

¸

¸

A

_

E

I

−E

A

+ω

+

_

B

¸

¸

ε

∗

λ

(k

) · p

¸

¸

I

__

I

¸

¸

ε

λ

(k) · p

¸

¸

A

_

E

I

−E

A

−ω

_

e

i(E

B

+ω

−E

A

−ω)t

(2.88)

This expression is of order e

2

, just as Equation (2.77) is. According

to Equation (1.85) we must add this result for λ

2

˙ c

(2)

f

(t) to the result

Equation (2.77) for λ˙ c

(1)

f

(t) to get ˙ c

f

(t) to order e

2

(second order in perturba-

tion theory). We then integrate over time from t

1

(at which time the system

is in the state

¸

¸

i

_

) to t to get c

f

(t) = λc

(1)

f

(t) +λ

2

c

(2)

f

(t) in the same manner

as done with Equation (1.95) in Section 1.3. Remember c

(0)

f

(t) = 0. Note

that Equation (2.77) and Equation (2.88) have the same time dependence

in their exponentials as they should, because the integration over time will

give δ-functions that impose energy conservation and the arguments of

the two should therefore be the same. We have the integral, common to

Equation (2.77) and Equation (2.88)

_

t

2

t

1

dt e

i(E

B

+ω

−E

A

−ω)t

(2.89)

We let t

1

→−∞and t

2

→+∞and use Equation (1.98) to get

_

+∞

−∞

dt e

i(E

B

+ω

−E

A

−ω)t

= 2π δ(E

B

+ω

−E

A

−ω) (2.90)

Quantum

Quantum

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd